Patent Perspective for Potential Antioxidant Compounds-Rutin and Quercetin - Sharma, Shrestha; K. Sahni, Jasjeet; Ali, Javed; Baboota, Sanjula (Recent Patents on Nanomedicine, 2013)
Recently, natural products are attaining a global interest as potential drug candidates due to better tolerance and minimum adverse drug reactions as compared to synthetic molecules. According to WHO estimation, about three-quarters of the world's population is consuming herbal products for various diseases including cancer, diabetes, human immunodeficiency, asthma and cardiovascular disorders. Various active ingredients are extracted from the herbs and formulated in different modern dosage forms, such as tablets, capsules, topical cream, gel, ointment and even some novel drug delivery forms, like extended release, sustained release, and microcapsule dosage forms. Therefore, patent filing of herbal formulations has increased over the past few years and scientific evidence of therapeutic activity has been reported by performing various in vitro and in vivo experiments. This manuscript deals with various patented herbal formulations of rutin and quercetin alone or in combination with other natural ingredients for various therapeutic activities such as antioxidant, antiviral, anti- inflammatory, anticancer, oedema and cardiovascular disorders. These formulations are available in various conventional dosage forms like tablet, capsule, troche, cream and syrups.
Keywords: quercetin